East Asian FDI in Europe and Germany - Siegfried Schultz (Intereconomics, 1995)
During the 1980s foreign direct investment (FDI) expanded remarkably. Simultaneously, the regional structure of foreign direct investment changed. This relationship is discernible among industrial countries, as well as between industrial and developing countries. Of particular importance is the interface of foreign trade relations between the “Triad” and the economically dynamic East Asian and Pacific area. This article highlights, in particular, foreign investment coming from Eastern Asia into Europe and Germany.
Keywords: 330; Foreign Direct Investment